Syntrophotalea acetylenivorans sp. nov., a diazotrophic, acetylenotrophic anaerobe isolated from intertidal sediments. Issue 3 (11th March 2021) - Baesman, Shaun M.; Sutton, John M.; Fierst, Janna L.; Akob, Denise M.; Oremland, Ronald S.
Abstract : A Gram-stain-negative, strictly anaerobic, non-motile, rod-shaped bacterium, designated SFB93 T, was isolated from the intertidal sediments of South San Francisco Bay, located near Palo Alto, CA, USA. SFB93 T was capable of acetylenotrophic and diazotrophic growth, grew at 22–37 °C, pH 6.3–8.5 and in the presence of 10–45 g l −1 NaCl. Phylogenetic analyses based on 16S rRNA gene sequencing showed that SFB93 T represented a member of the genus Syntrophotalea with highest 16S rRNA gene sequence similarities to Syntrophotalea acetylenica DSM 3246 T (96.6 %), Syntrophotalea carbinolica DSM 2380 T (96.5 %), and Syntrophotalea venetiana DSM 2394 T (96.7 %). Genome sequencing revealed a genome size of 3.22 Mbp and a DNA G+C content of 53.4 %. SFB93 T had low genome-wide average nucleotide identity (81–87.5 %) and <70 % digital DNA–DNA hybridization value with other members of the genus Syntrophotalea . The phylogenetic position of SFB93 T within the family Syntrophotaleaceae and as a novel member of the genus Syntrophotalea was confirmed via phylogenetic reconstruction based on concatenated alignments of 92 bacterial core genes. On the basis of the results of phenotypic, genotypic and phylogenetic analyses, a novel species, Syntrophotalea acetylenivorans sp. nov., is proposed, with SFB93 T (=DSM 106009 T =JCM 33327 T =ATCC TSD-118 T ) as the type strain.